Toward Green, Clean and Sustainable Environment - Bedjo Santoso; Siti Aisiyah Suciningtyas; Provita Wijayanti (International Conference on Coastal and Delta Areas, 2017)
The purpose of this paper is to create an appropriate waste management model for UNISSULA that proclaim a clean, green and sustainable environment based on waste processing for economic value and ecological enviroment. A brief overview of the concept includes development of management system of regional waste, education & waste management & WMS training, waste handling, waste processing and utilization of waste processing products. However, UNISSULA's concept has some weaknesses that must be overcome in order this concept could be running well such as: capacity of garbage, area, infrastucture (grabage fleet) and smart cards and automatic container system. It is therefore, needed cooperation with Semarang City Government' that is by collaboration concept of UNISSULA with Semarang City Government’s concept to ensure the input capacity, and people support. As a result, the creation of a vicious circle of urban rubbish management namely, economic stimulation, clean environment, government income and people income and economic structure. Besides that, this concept is expected to improve economic citizen through economic value added of waste. The next is expected to change the culture, urban lifestyle, green behavior, clean environment, transportation and income, and farming, fruits and vegetables industry. Keywords:Waste Management, Value added, Clean Environment, Sustainable Growth.